2012
DOI: 10.5267/j.msl.2012.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A survey relation of organizational culture and organizational citizenship behavior with employees’ empowerment

Abstract: The aim of this study is to study the relationship between organizational culture and organizational citizenship behavior (OCB) with employees' empowerment. Empowering employee's breeds success by providing a suitable framework to utilize the necessary skills in an attempt to realize organizational goals. In this paper, four dimensions of employees' empowerment including meaningfulness, choice, competence and impact are investigated. We also identify four dimensions for organizational culture including adaptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Organizational citizenship behavior is a set of voluntary behaviors, which does not count as the official duties of the person, but are done by them, and could lead to improved efficiency of tasks and organization roles ( 10 ). This term is defined with words such as good soldiers, arbitrary behavior, voluntary behavior, and the exit of the task behavior, which created a new movement in the organization vision, especially in the field of organizational behavior, which has a critical role in organizational efficiency ( 11 ). Batman and Organ (1983) presented the concept of organizational citizenship behavior to the world of science ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational citizenship behavior is a set of voluntary behaviors, which does not count as the official duties of the person, but are done by them, and could lead to improved efficiency of tasks and organization roles ( 10 ). This term is defined with words such as good soldiers, arbitrary behavior, voluntary behavior, and the exit of the task behavior, which created a new movement in the organization vision, especially in the field of organizational behavior, which has a critical role in organizational efficiency ( 11 ). Batman and Organ (1983) presented the concept of organizational citizenship behavior to the world of science ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment is a set of policies helping self-managing teams and individuals become in charge of careers and destinies. Empowering employee's breeds success by giving the framework to the workforce to unleash, to develop, and to utilize skills to realize organizational objectives (Sadati, 2012). Empowerment is a type of a journey to a destination (Kaye & Jordan-Evans, 2002) and today's business environment needs administrators to visualize the direction the organization very clearly (Baird, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that there was no correlation among structural components in engineering and administration areas. Sadati (2012) performed a survey relation of organizational culture and organizational citizenship behavior with employees' empowerment. He studied the relationship between organizational culture and organizational citizenship behavior (OCB) with employees' empowerment.…”
Section: Introductionmentioning
confidence: 99%